Eosinophilic granuloma of the skin. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
Eosinophilic granuloma is part of the clinical spectrum of Langerhans cell histiocytosis (LCH), that ranges from congenital LC histiocytoma, to congenital LCH Hashimoto-Pritzker type, to acquired self-healing LCH till to multisystem acquired LCH without or with organ dysfunction. Eosinophilic granuloma, usually involving the bone, is often diagnosed after the second year of life; its clinical course is favorable towards the remission, which is spontaneous or favored by curettage or radiation therapy. The skin can be affected in contiguity with the bone lesions or even at a distance, more often in periorificial sites (1). The primary involvement of the skin is rather exceptional (2). Its prognosis is good by analogy to eosinophilic granuloma of the bone. However, the rarity of published cases suggests careful clinical monitoring.